Comparative Performance of Broiler Fed Diets Containing Raw and Processed Mucuna Seed Meal - Tuleun , C.D.; Offia, B.; Yaakugh, I.D.I. (International Journal of Poultry Science, 2010)
The effects of raw and local processing methods on the nutritive value of Mucuna utilis seeds fed in diets to broiler performance were investigated. The processing methods were: seeds were soaked for 24 h in plain water, cooking of 24-h pre-soaked seeds for 60 min and cooking in a solution of potash (kanwa, trona) for 60 min. Five experimental diets were formulated such that diet 1 contained no mucuna (control), while raw, soaked, pre-soaked and cooked and cooked-in-potash mucuna seed meal were included at 20% dietary levels respectively. One hundred and fifty (150) 0ne-week old (Anak, 2000) broiler chicks were randomly assigned to the experimental diets in a completely randomized design. There were 3 replicates of the 5 treatments and 10 birds per replicate. 22% Crude Protein (CP) diets were fed during the starter phase and 20%CP diets during the finisher phase. Feed and water were supplied ad libitum throughout the 8-week trial period. At the end of the feeding trial, 3 birds were selected from replicates and slaughtered for carcass and blood evaluation. The different processing methods caused percentage reductions in Crude Protein (CP) and ether extract but increased the gross energy and ash content of the seeds. Cooking of pre-soaked beans and cooking in potash solution significantly (p